Effect of negative parallax in VLBI - Osetrova, A. A. (2025)
Extragalactic radio sources, observed with Very Long Baseline Interferometry (VLBI), are used to define the International Celestial Reference System (ICRS). Its latest realization, ICRF3, based on observations from 1979 to 2018, includes coordinates for 4,536 sources, 303 of which are "defining” and determine the ICRS axes with an accuracy of 30 Ras. Otherwise, the Gaia optical astrometry mission has measured precise positions of millions of objects, including QSOs also observed by VLBI. In Gaia EDR3, a negative parallax effect for QSOs having a median amplitude of -17 Ras was reported, likely caused by technical reasons. We analyzed the full set of VLBI observations spanning from 1993 to 2025 and discovered the similar parallax effect using two methods: global parameter estimation, and through positional time series analysis. We compared the parallactic effect in VLBI and Gaia EDR3 for the same period of time (2014 - 2017). The results showed that the parallax estimated as -16.8 ± 2.5 Ras in VLBI is in good agreement with the Gaia EDR3 value.This consistency suggests that both effects may share a common origin. Also, time series of individual sources reveal an annual signal in the periodgrams. Cross-spectral analysis indicates a strong correlation between the right ascension and declination components of this signal. The amplitude of the annual variation ranges approximately from +20 to -70 Ras. We assume that this parallax effect may originate due to the deformation of the fundamental axes, possibly caused by the positional instability of the ICRF3 «defining» sources.